Overview of Muhammadiyah Members' Knowledge Level Regarding the Halal Status of Medicines in the Peniron Branch - Irfangi, Irfangi; Muchromin , Muchromin; Sodik, Anwar (Sean Institute, 2024)
Indonesia, as the country with the largest Muslim population in the world, places significant importance on the halal status of products, including medicines. This study aims to understand the community's knowledge about the halal status of medicines in the Peniron Muhammadiyah Branch, Kebumen Regency. The research method used is descriptive with an observational approach. The sample consists of all members of PRM Peniron who hold membership cards. Data were collected using a five-point Likert scale questionnaire and analyzed to measure knowledge about halal medicines. The results show that the majority of respondents have a good understanding of the meaning of halal and Islamic law regarding the halal-haram status of medicines. However, some aspects are still poorly understood, such as the halal medicine production process and MUI halal regulations. About 15-20% of respondents are unaware that medicinal syrups contain alcohol and that medicine capsules can be made from pig-derived gelatin. Furthermore, there is a lack of understanding regarding MUI's regulations on permissible alcohol content and the use of pig-derived insulin in emergency situations.The conclusion of this study highlights the need for further socialization and education on halal materials and regulations in medicines to enhance community understanding. The community strongly supports the acceleration of halal labeling for medicines in Indonesia to ensure compliance with Islamic Sharia principles.